2020
DOI: 10.1021/acsaem.0c01378
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Trap and Polydispersity in Mutually Passivated Quantum Dot Solar Cells

Abstract: Control over surface passivation is a key to manage the optoelectronic properties in low-dimensional nanomaterials because of their high surface-to-volume ratios. Tunable band gap quantum dots (QDs) are a potential building block for the development of optoelectronic devices like solar cells, photodetectors, and light-emitting diodes. Long and insulating surface ligands of colloidally synthesized QDs are exchanged by short ligands to attain compact arrangement in thin films to facilitate the charge transport p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…However, an increase in CPT concentrations beyond 10 mM does not yield higher lifetime values for the photogenerated carriers. The density of trap states in the solar cells determined from the reported transient photovoltage and transient current decay measurements ,, shows a similar trend (Figure S7b). The −I passivated solar cells show higher trap densities than hybrid passivated solar cells; however, there is no noticeable decrease in trap densities for higher CPT concentrations.…”
Section: Results and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, an increase in CPT concentrations beyond 10 mM does not yield higher lifetime values for the photogenerated carriers. The density of trap states in the solar cells determined from the reported transient photovoltage and transient current decay measurements ,, shows a similar trend (Figure S7b). The −I passivated solar cells show higher trap densities than hybrid passivated solar cells; however, there is no noticeable decrease in trap densities for higher CPT concentrations.…”
Section: Results and Discussionsupporting
confidence: 55%
“…The density of trap states (DOS) is determined using the reported TPV and TPC methods. ,, By integrating the area under a TPC curve, the number of charge carriers generated by the light pulse is calculated. The differential capacitance is determined using the formula , where Δ q is the number of photogenerated carriers (determined from the TPC curve) and Δ V oc is the corresponding change in V oc due to the light pulse.…”
Section: Methodsmentioning
confidence: 99%
“…With the n-i-p structure, the CQDSC with hybrid ligands can achieve a V oc of 0.61 V, which is 40 mV higher than that with single iodide ligands (improved by 7%), and the V oc loss reaches ≈0.52 V. Additionally, Sargent group [66] proposed to treat CQD surface with organic ligands to prepare p-type CQD via hybrid passivation. With n-i-p structure, the CQDSC with hybrid ligands (p-type CQD) can achieve a V oc of 0.68 V, which is 50 mV higher than that with single halide ligands (improved by 8.1%), and the V oc loss drops to ≈0.45 V. Similarly, Sharma et al [126] also performed the hybrid passivation (iodide and methyl mercapto propionate) to achieve lower CQD surface defect density and higher V oc , indicating the robustness of this strategy. The CQDSC performance with different ligands is summarized in Table 3.…”
Section: Direct Passivationmentioning
confidence: 89%
“…With n–i–p structure, the CQDSC with hybrid ligands (p‐type CQD) can achieve a V oc of 0.68 V, which is 50 mV higher than that with single halide ligands (improved by 8.1%), and the V oc loss drops to ≈0.45 V. Similarly, Sharma et al. [ 126 ] also performed the hybrid passivation (iodide and methyl mercapto propionate) to achieve lower CQD surface defect density and higher V oc , indicating the robustness of this strategy. The CQDSC performance with different ligands is summarized in Table 3 .…”
Section: Solar Absorbermentioning
confidence: 92%
“…Sargent and co-workers found that PbI 3 – -shelled PbS nanocrystals allowed fabrication of nanocrystal solar cells with power conversion efficiencies of 8.95%, a major advancement for nanocrystal devices . Halometallate ligation has subsequently been employed in other nanocrystal optoelectronic devices. …”
mentioning
confidence: 99%